The politics of community resilience-building in Laguinbanwa, Ibajay, Aklan. - Andres, Darine Jane R.; Venus, Ervin Ralph S. (2016.)
Community resilience is the ability of the community system and its component parts to anticipate, absorb, accommodate or recover from the effects of a hazardous event in a timely and efficient manner, while ensuring the preservation, restoration, or improvement of its essential basic structures and functions (IPCC, 2012). This research focuses on the politics of community resilience-building in Laguinbanwa, Ibajay, Aklan. A review of secondary data, thematic analysis of interviews and quantitative survey were done to assess the physic-environmental, economic-human, socio-cultural and politico-institutional contexts in the barangay before and after Typhoon Yolanda. Public policy changes and lesson learned following the effects and damages brought by the typhoon were identified and analyzed. Analysis of the coordination among stakeholders including the local community, barangay council, LGUs, NGOs and national agencies were done to unfold the politics of resilience building. The results revealed that there are significant changes in DRR-CCA policies of the state actors and increased local knowledge on disasters among the stakeholders affecting their actions on DRR-CCA policies and programs. The observed attempts at coordination and organizational linkages among stakeholders facilitate the over-all development of the barangay creating a more resilient community.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Politics -- Laguinbanwa, Ibajay, Aklan; Community Resilience-Building.